Peran Pengambilan Keputusan Etis dalam Mewujudkan Good Governance (Studi Kasus Suap Hakim Agung SD) - Suryani, Eny; Nugroho, Kandung Sapto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2024)
Ethical judgment is a major concern especially in the public sector. Unethical incidents (one of which is a bribery case involving a Supreme Court Judge) hinder the realization of good governance. This article discusses the phenomenon of bribery by taking a perspective from the ethical decision-making model. Ethical decision-making can ultimately encourage the realization of good governance. Through a qualitative approach and using secondary data and related literature, this article explains how the ethical decision-making model according to Jamest Rest's four-component model can help prevent and eradicate corruption. By strengthening ethics education, transparency, accountability, enforcing the law, and encouraging public participation, it is hoped that a strong foundation can be built to realize good governance,